Effects of Nitrogen Addition on Leaf Functional Traits of Dominant Species in Bayanbulak Grassland, Xinjiang, China - Ding, Xiaoyu; Liu, Junjie; Wang, Yao; Wang, Juan; Liu, Chao; Qin, Mengtian; Xu, Yujiao; Ma, Yonggang; Yang, Jianjun; Xu, Zhonglin (Plants (Basel), 2025)
Nitrogen inputs exert significant impacts on plant species composition and ecosystem stability within alpine grasslands. The exploration of leaf functional traits holds great potential in uncovering plants' adaptive strategies and competitive edges, and is pivotal in comprehending the ramifications of nitrogen inputs on biodiversity. In this study, the Bayanbulak grassland was selected as the research subject to investigate the impact of nitrogen addition on leaf functional traits of different plant functional groups. Specifically, various gradients of nitrogen addition were established to observe changes in leaf dry matter content (LDMC) and leaf area (LA) among three distinct plant functional groups. Furthermore, structural equation modeling (SEM) was employed to analyze the pathways through which nitrogen addition influenced the LDMC of these plant functional groups. The results were as follows: (1) LA and leaf length (LL) of Poaceae changed significantly ( < 0.05) under different N addition gradients, and leaf nutrient contents of Poaceae, Rosaceae and Fabaceae showed significant changes under different N addition gradients. (2) Pearson correlation analyses showed that total nitrogen (TN), total carbon (TOC) and leaf width (LW) of Rosaceae leaves had a significant positive correlation, and the TOC and total phosphorus (TP) of Fabaceae leaves showed a significant negative correlation. (3) SEM of the three plant functional groups showed direct and indirect effects of N addition on leaf dry matter content of Poaceae and Rosaceae, and only indirect effects on Fabaceae.